Practitioners’ perspective: a mixed-methods study on dealing with suicidality from the perspective of oncological healthcare professionals - Tamara Schwinn; Judith Hirschmiller; Jörg Wiltink; Rüdiger Zwerenz; Elmar Brähler; Manfred E. Beutel; Mareike Ernst (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose Healthcare professionals (HCPs) play a critical role in suicide prevention and clinical guidelines recommend inquiring about suicidality as part of medical history and diagnosis. Emerging evidence indicates a lack of implementation of such policies in clinical practice. However, to date, no comprehensive mixed-methods study has examined this issue in the field of oncology. Methods A preregistered mixed-methods study was conducted with oncological HCPs (N = 20) from various professions, using semi-structured interviews and validated questionnaires. Employing an explorative theory-generating approach, qualitative content analysis was applied to the interviews. The different data sources are integrated and contrasted. Comparisons according to sociodemographic variables (profession, age, and gender) and frequency distributions were used to examine the questionnaire data. Results Most HCPs reported direct or indirect experiences with suicidality in cancer patients. Nineteen HCPs did not routinely explore suicidality, of whom five reported not inquiring about it at all. Those who explored suicidality were more confident, less emotionally overwhelmed and reported higher subjective knowledge. HCPs also differed regarding their endorsement of suicide myths. Conclusion The study highlights difficulties with active suicide exploration and differences among HCPs. Integrating these findings into education and training could improve HCPs’ skills and reduce disparities, supporting successful suicide prevention.